De novo intronic GATA1 mutation leads to diamond-blackfan anemia like disease - Liu, Shan; Pei, Kunlin; Chen, Lu; Wu, Jing; Chen, Qiuling; Zhang, Jinyan; Zhang, Hui; Wang, Chengyi (Frontiers in Genetics, 2023)
GATA1 is required for normal erythropoiesis. Exonic/intronic GATA1 mutations causes Diamond-Blackfan Anemia (DBA)-like disease. Herein, we present a case of a 5-year-old boy with anemia of unknown etiology. Whole-exome sequencing revealed a de novo GATA1 c.220+1G>C mutation. The reporter gene assay revealed that such mutations did not affect on GATA1 transcriptional activity. The normal transcription of GATA1 was disturbed, as evidenced by increased expression of the shorter GATA1 isoform. RDDS prediction analysis revealed that abnormal GATA1 splicing might be the underlying mechanism disrupting GATA1 transcription, thereby impairing erythropoiesis. Prednisone treatment significantly improved erythropoiesis, evidenced by increased hemoglobin and reticulocyte counts.